Anti-platelet factor 4/polyanion antibodies mediate a new mechanism of autoimmunity - Thi-Huong Nguyen (Nature Portfolio, 2017)
Antibodies against the platelet factor 4 (PF4) support bacterial host defence but in some cases may lead to heparin-induced thrombocytopenia (HIT). Nguyenet al.show that in autoimmune HIT a subset of antibodies binds strongly to PF4 causing its conformational change that leads to association of non-pathogenic PF4 antibodies and thrombotic platelet activation.